Parallel Evolution in Pseudomonas aeruginosa over 39,000 Generations In Vivo - Huse, Holly K. (American Society of Microbiology, 2010)
The Gram-negative bacterium Pseudomonas aeruginosa is a common cause of chronic airway infections in individuals with the heritable disease cystic fibrosis (CF). After prolonged colonization of the CF lung, P. aeruginosa becomes highly resistant to host clearance and antibiotic treatment; therefore, understanding how this bacterium evolves during chronic infection is important for identifying beneficial adaptations that could be targeted therapeutically. To identify potential adaptive traits of P. aeruginosa during chronic infection, we carried out global transcriptomic profiling of chronological clonal isolates obtained from 3 individuals with CF. Isolates were collected sequentially over periods ranging from 3 months to 8 years, representing up to 39,000 in vivo generations. We identified 24 genes that were commonly regulated by all 3 P. aeruginosa lineages, including several genes encoding traits previously shown to be important for in vivo growth. Our results reveal that parallel evolution occurs in the CF lung and that at least a proportion of the traits identified are beneficial for P. aeruginosa chronic colonization of the CF lung.